Budidaya Sayuran Organik Secara Vertikultur di Pekarangan - Edy Kustiani; Eko Yuliarsha Sidhi; Virgian Galuh Agusty (Kadiri University, 2021)
Vegetables are an essential commodity as a source of vitamins and minerals for the community, so they must be available in sufficient quantities, at low prices, and are organic products. The vegetables produced are healthy. Utilizing the yard to meet the family's vegetable needs can be done by vertical cultivation using PVC drainpipes,